Lipid Peroxidation in Judoists Using Oral Contraceptives - Massart, A.; Portier, H.; Rosado, F.; Toumi, H.; Filaire, E. (International Journal of Sports Medicine, 2012)
12 female judoists using oral contraceptives (OCU) containing 0.03 mg ethinylestradiol and 3 mg drospirenone for 20±12 months (mean±SD) were compared with a control group of 14 judoist noncontraceptive users (NCU) in order to evaluate resting (T1) and postexercise (T2) lipid peroxidation (LPO) and antioxidant parameters. Data were collected 20 min before and 10 min after a morning session of judo training and included determination of lag phase (Lp) before free radical-induced oxidation, glutathione peroxidase (GPx), α-tocopherol, retinol, and oxidative stress markers related to LPO. Significantly higher resting oxidative stress (+125.8 and +165.2% for malondialdehyde and lipid peroxides, respectively) and lower values of Lp and GPx ( − 23.4 and  − 12.1%, respectively) were observed in the OCU compared with NCU. The judo training session induced an increase in plasma LPO whatever the treatment. We noted significant increases in Lp (+14.7%; p<0.05 vs. preexercise) and GPx (22.1%; p<0.05 vs. preexercise) only in the NCU group. We suggest that a judo training session favourably altered some antioxidants in NCU but not in OCU. As excessive oxidative stress is linked to the development of several chronic diseases, the use of agents to reduce antioxidants may be reasonable in OCU.
Keywords: contraceptive pill; oxidative stress; exercise; antioxidant